Antibacterial and antifungal study of saponin extracted from rambutan leaves - Salmina Barvin, Md Sameenudeen (2025)
The study investigates the antibacterial and antifungal properties of saponins extracted from rambutan leaves (Nephelium lappaceum). While the extract demonstrated significant antibacterial activity against Gram-positive and Gram-negative bacterial strains, it showed no inhibitory effects against fungal strains, such as Candida albicans and Aspergillus niger. These findings suggest that rambutan leaf saponins have potential as natural antibacterial agents, offering an alternative to synthetic antibiotics in addressing bacterial resistance. The extraction techniques employed— maceration and liquid-liquid extraction—were effective in isolating bioactive compounds. Further research is recommended to explore its antibacterial mechanisms and optimize its applications.